Pengaruh Modal Intelektual, Inflasi, dan Dana Pihak Ketiga terhadap Manajemen Laba.: (Studi Empiris pada Bursa Efek Indonesia (BEI)) - Nur Mediana Wahab Ali; Herman Darwis; Gregorius Jeandry (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
Every year, companies are required to prepare financial reports that include information on their financial condition, performance, and cash flow. This report demonstrates management's accountability for the resources they manage. One of the most important elements in this report is profit. This profit figure is closely monitored by report users, as it is considered a key measure of management's achievements and performance. However, in their financial management, manufacturing companies often face problems related to earnings management practices. Earnings management is an attempt by company management to manipulate or arrange financial reports, especially profits, for specific purposes. This practice can be carried out to demonstrate better financial performance, meet market targets, or reduce tax burdens. The purpose of this study is to determine the determinants of earnings management, such as intellectual capital, inflation, and third-party funds. This study utilizes information taken from the financial reports of manufacturers listed on the Indonesia Stock Exchange (IDX) using a purposive sampling method that meets the exploratory steps. This research period was taken over three years, with 78 observations used from 26 manufacturing companies. This research method used Eviews 12 with secondary data types. The results of the study show that there is a positive influence between intellectual capital on profit management, and there is no influence of inflation on profit management, and third party funds do not have a significant influence on profit management..